RESPON PESERTA DIDIK SMP TERHADAP PENGGUNAAN MODEL PROBLEM BASED LEARNING PADA MATERI GERAK LURUS - Rahmadani, Destia; Tandililing, Edy; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe aim of this study was to determine student responses about the use of problem based learning models (PBL) on straight motion matter. Data was taken by questionnaire of student's response that gave after the learning process end. Data analyse was used by percentage. There are 28 students from SMPN 8 Pontianak involved in this research. Indirect communication techniques are used to collect data. The research resulst showed that, more than 70% gave a positive response to use of problem based learning models (PBL) on straight motion matter. They further showed that: (1) the use of PBL models on creative thinking skills (79.5%) with good category, (2) the PBL model learning process (86%) with very good category, (3) the benefits of PBL models on the material of Straight Motion (83.5%) with very good category, (4) Impact of PBL models on creative thinking skills (77.25%) with good category, and (5) Creative thinking skills related to Straight Motion matterl (75%) with good category.Â Keywords: Problem Based Learning, Straight Motion, Student's Response